STRATEGI PENGELOLAAN BANTUAN OPERASIONAL SEKOLAH DASAR DALAM MENGOPTIMALKAN MEDIA PEMBELAJARAN DI SD NEGERI 173330 SIBUNTUON KECAMATAN LINTONGNIHUTA KABUPATEN HUMBANG HASUNDUTAN - Tanggapan C. Tampubolon; Kaleb e. Simanungkalit; Humiras Betty M. Sihombing (LPPM Universitas Darma Agung, 2021)
This study aims to analyze the strategy of managing school operational assistance in optimizing learning media at SD N. 173330 Sibuntuon, Lintongnihuta District. Data collection techniques were carried out using observation, documentation and in-depth interviews. Data analysis techniques by reducing data, displaying data, and drawing conclusions. This study uses source and technical triangulation as well as theory to find the validity of the data. The results of the research at SD N. 173330 Sibuntuon show that: 1) the strategy for managing school operational assistance in optimizing learning media is carried out with the stages of budget planning (budgeting), budget procurement, budget allocation (allocating), budget use by prioritizing media, learning materials and tools , make bookkeeping (accounting), supervision and accountability following the technical guidelines for BOS; 2) The problems of the school operational assistance management strategy are: a) teachers do not want to actively participate in the process of making RKAS, b) learning media that have been damaged by the time the fiscal year is running, c) lack of understanding of teachers about the technical guidelines for the use of BOS funds, d) some teachers cannot operate learning media, e) the ability of employees to repair damaged learning media. 3) Efforts to overcome the problems of managing School Operational Assistance are a) communication between teachers and the BOS treasurer, b) managing finances, prioritizing learning media that are more important and will be used soon, c) libraries add reading materials, d) provide guidance to teachers about how to use learning media.